FIXED POINT THEOREM AND SUB-COMPATIBILITY IN FUZZY METRIC SPACE - Arihant Jain, V. K. Gupta, Rambabu Dangi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
In this paper, the concept of sub-compatibility in fuzzy metric space has been applied to prove a common fixed point theorem for six self maps using implicit relation. Our result generalizes and extends the result of Ranadive and Chouhan [13].